2011
DOI: 10.1530/eje-11-0518
|View full text |Cite
|
Sign up to set email alerts
|

Grapefruit juice and licorice increase cortisol availability in patients with Addison's disease

Abstract: Objective: Failure to mirror the diurnal cortisol profile could contribute to the impaired subjective health status in Addison's disease (AD). Some patients report benefit from the use of various nutritional compounds. The objective of this study was to investigate the impact of licorice and grapefruit juice (GFJ) on the absorption and metabolism of cortisone acetate (CA). Design: Patients (nZ17) with AD on stable CA replacement therapy were recruited from the outpatient clinic at Haukeland University Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 43 publications
3
25
0
Order By: Relevance
“…Chemical structures of licorice compounds (isolated from Glycyrrhiza uralensis Fisch.). The compounds were 4-hydroxybenzoic acid (1), phloretic acid (2), liquiritin apioside (3), liquiritin (4), isoliquiritin apioside (5), isoliquiritin (6), ononin (7), 4′,7-dihydroxyflavone (8), liquiritigenin (9), licoricesaponin A3 (10), licopyranocoumarin (11), echinatin (12), naringenin (13), genistein (14), licorice-saponin G2 (15), licorice-saponin E2 (16), 3-methylkaempferol (17), davidigenin (18), glycyrrhizic acid (19), isoliquiritigenin (20), 7,4′-dihydroxy-3′-methoxyisoflavan (21), formononetin (22), glycycoumarin (23), semilicoisoflavone B (24), kumatakenin (25), licoisoflavone A (26), licoricone (27), isolicoflavonol (28), lupiwighteone (29), glycyrol (30), glyurallin A (31), licoflavonol (32), topazolin (33), glycyrin (34), gancaonin I (35), angustone A (36), isoangustone A (37), gancaonin G (38), 6,8-diprenylgenistein (39), and 18β-glycyrrhetinic acid (40). Api apinose, GluA glucuronic acid, Glc glucose, Prenyl isoprenoid.…”
Section: Lc/ms/ms Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical structures of licorice compounds (isolated from Glycyrrhiza uralensis Fisch.). The compounds were 4-hydroxybenzoic acid (1), phloretic acid (2), liquiritin apioside (3), liquiritin (4), isoliquiritin apioside (5), isoliquiritin (6), ononin (7), 4′,7-dihydroxyflavone (8), liquiritigenin (9), licoricesaponin A3 (10), licopyranocoumarin (11), echinatin (12), naringenin (13), genistein (14), licorice-saponin G2 (15), licorice-saponin E2 (16), 3-methylkaempferol (17), davidigenin (18), glycyrrhizic acid (19), isoliquiritigenin (20), 7,4′-dihydroxy-3′-methoxyisoflavan (21), formononetin (22), glycycoumarin (23), semilicoisoflavone B (24), kumatakenin (25), licoisoflavone A (26), licoricone (27), isolicoflavonol (28), lupiwighteone (29), glycyrol (30), glyurallin A (31), licoflavonol (32), topazolin (33), glycyrin (34), gancaonin I (35), angustone A (36), isoangustone A (37), gancaonin G (38), 6,8-diprenylgenistein (39), and 18β-glycyrrhetinic acid (40). Api apinose, GluA glucuronic acid, Glc glucose, Prenyl isoprenoid.…”
Section: Lc/ms/ms Assaymentioning
confidence: 99%
“…For instance, oral intake of 7.5 g/kg licorice could increase the area under plasma concentration-time curve (AUC) of methotrexate by 127% and extend the mean residence time from 240 to 921 min (11). Licorice has also been reported to alter the pharmacokinetics of drugs like warfarin (8), cyclosporine (12), and cortisol (13). Therefore, NIH has indicated that licorice "might have moderate effect on medications changed by the liver cytochrome P450 2C9 and 3A4" (10).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, partial preservation of cortisol secretion in some AD patients has been documented (27,28,29), which possibly correlates with adrenal medullary function and could partly explain the large diversity in fatigue after stress and propensity to adrenal crisis.…”
Section: European Journal Of Endocrinologymentioning
confidence: 96%
“…Inhibitors of cytochrome P450 accelerate the catabolism of fludrocortisone; conversely inhibitors of cytochrome P450 such as phenytoin and phenobarbital reduce catabolism. Licorice and grapefruit juice both potentiate the mineralocorticoid action of hydrocortisone and thus should be avoided [67].…”
Section: Drug Interactionsmentioning
confidence: 99%